MENGENAL FRAMEWORK UNDERSTANDING BY DESIGN DALAM KEGIATAN PEMBELAJARAN YANG EFEKTIF - Abdi Putra Siregar; Wayan Siskasari; Zainal Efendi Hasibuan (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2024)
Recognizing the Understanding by Design (UbD) framework in learning processes or activities is an interesting thing to discuss. Especially in the era of the implementation of the independent curriculum implementation that is being launched by the Minister of Education. This research aims to analyze information related to the introduction of the Understanding by Design (UbD) framework. The research method used is the library research. Data is taken by collecting literature from both journals and books related to UbD. The results of the research are intended to be a treasury of scientific knowledge in introducing the framework of understanding by design. This research also emphasizes the importance of knowing UbD to achieve meaningful, purposeful and quality learning.